XX зууны сүүл үеийн Монгол-Халимагийн харилцаа (Journal of International Studies, 2015)
Энэхүү өгүүлэлд Монгол-Халимагийн XX зууны сүүл үеийн харилцааны өрнөл хөгжлийг улс төр, шинжлэх ухаан, соёл, хөдөө аж ахуйн харилцаа хамтын ажиллагааны жишээн дээр хураангуйлан авч үзээд нэгтгэн дүгнэх оролдлого хийсэн болно. Mongolia Kalmykia relations at the end of 20th CenturyAbstract: This paper considered about the relationship between Mongolia and Kalmykia in the end of the XX century. During that time, Mongolia and Kalmykia had supported the traditional relationship set during the socialist time and cooperated actively on exchanging high level representatives, making official visits, and making agreements. Kalmykia had intended to cooperate on the fields of politics, science and culture while Mongolia had had a strong interest on collaboration of agriculture and economy.